Obteniendo Resultados 2004 Promoción de Responsabilidad a Través de Métodos y Herramientas de Planeación, Implementación y Evaluación - Chinman, Matthew (RAND Corporation, 2005)
Incorporating traditional evaluation, empowerment evaluation, results-based accountability, and continuous quality improvement, this manual's ten-step process enhances practitioners' substance abuse prevention skills while empowering them to plan, implement, and evaluate their own programs. The manual's text and worksheets address needs and resources assessment; goals and objectives; choosing programs; ensuring program "fit"; capacity, planning, process, and outcome evaluation; continuous quality improvement; and sustainability.